Antidiarrhoeal Activity of Methanolic Stem Bark Extract of Sarcocephalus latifolius in Castor Oil-Induced Diarrhoeal Albino Rats - Ahmed, Maryam Usman; Titus, Diowato; Isa, Ruqayya (African Journal of Biochemistry and Molecular Biology Research, 2024)
Diarrhoea remains one of the leading causes of death among children in developing countries characterized by frequent passing of watery faeces. This study eval_uates the antidiarrhoeal activities of Sarcocephalus latifolius in castor oil-induced diarrhoeal albino rats. Thirty (30) albino rats were divided into six groups of five rats each. Except group 1 (control group) which received distilled water, all groups received 0.5 mL castor oil to induce diarrhoea. Group 2 received loperamide 3 mg/kg b. wt. Group 3, 4, 5, and 6 received 100, 200, 300, and 400 mg/kg b. wt. respectively of the methanolic stem bark extract of Sarcocephalus latifolius. Total diarrhoeic faeces, stool inhibition, intestinal fluid accumulation, and intestinal transit was determined to eval_uate the antidiarrhoeal effect of the extract. Total diarrhoeal faeces, intestinal content and intestinal transit reflects significant (p<0.05) decrease with increase in the dose of the extract, group 4 which received high dose (400 mg/kg b. wt.) shows no significant difference when compared with group 2 which received loperamide. Percentage inhibition increases with increase in dose. Methanolic stem bark extract of S. latifolius possess antidiarrhoeal effect on castor oil-induced diarrhoea.